Songs of Eastern Europe [bladmuziek] : a collection of 100 Volkslieder of Austria, Bohemia, Hungary, Servia, Turkey, and other countries - Kappey, Clara; Kappey, J.A. (London : Boosey)
Bibliotheek Camille Huysmans
Engels
Partituur
Keywords: volksliederen; Oost-Europa.